PROFILE OF NUTRITIONAL AND DEVELOPMENTAL STATUS OF UNDER FIVE YEARS OLD CHILDREN IN TANJUNG KARANG DISTRICT, MATARAM, INDONESIA - Zulfikar Ihyauddin; Jeslyn Tengkawan; Ayu Anandhika Septisari; Nurhandini Eka Dewi; Titi Pambudi Karuniawaty (Media Gizi Indonesia, 2020)
To improve the human capacity in West Nusa Tenggara (WNT) province, a community-based intervention called Generasi Emas NTB (GEN) has been implemented in 2014. One of the programs is to ensure children’s nutritional and developmental wellbeing. However, there remains limited information regarding the situation of nutritional and developmental status of the children living in the GEN villages. This study aimed to assess the nutritional and developmental situation of under-fi ve years old children living in Tanjung Karang district, WNT. A cross-sectional study was conducted in Tanjung Karang district, one of the GEN villages in WNT, through integrated post service (posyandu). Children who met the sampling criteria were screened for their nutritional status using anthropometric measurement and developmental status using a prescreening developmental questionnaire (KPSP). A total of 638 children completed the demographic baseline assessment and were enrolled as participants. Most of the children were in the age group 7-12 months (19.1%) and 25-36 months (19.4%). The proportion of children who were underweight, stunting, and wasting were 19.4%, 32.2%, and 8.0%, respectively. The fi ndings for developmental screening showed that 12.2% children had dubious development and 3.1% (20/638) children were suspect of having a developmental delay. The proportion of under-fi ve years old children in Tanjung Karang district who were underweight, stunting, and wasting were still high but lower than the provincial average prevalence in 2017. Children who were found to have a doubtful result and suspect to have a developmental delay need to be evaluated further.